Estudo de distorções em soldagem com uso de técnicas numéricas e de otimização - Araújo, Douglas Bezerra de (2012)
The occurrence of distortions of structures is common during welding. Such distortions are more severe in the case of large structures, such as shipbuilding. Since distortions can increase manufacturing costs and time during shipbuilding, a thorough study of causes and consequences of distortions is necessary. Therefore, this work aims to study the distortion phenomenon during welding processes and contribute to ship construction by using numerical and experimental techniques. This work can be split into two steps, in which factors that cause distortions were explored by using numerical approach. The first step was the investigation of distortion occurrence in simple structures, namely common joints employed in welding. The influence of joint type on thermal efficiency, restrictions (boundary conditions) on T joint, heat input and rotational-distortion geometry was also investigated. Afterwards, experimental runs for model calibration were carried out by using inverse method of Differential Evolution (DE) for estimating the parameter of Gaussian-heat distribution. Temperature fields were measured by thermocouples and infrared camera with previous emissivity calibration during weldments. The second step was the simulation of complex structures similar to panels made by thin plate and T joints (reinforcement) commonly found in naval construction. These complex structures are. The initial conditions for the simulation of complex structures were the forces calculated by simulation on the simple structures (basically T joints). This technique is called equivalent forces . The simulations were validated by experimental runs, in which a panel was welded and displacement measured by three-dimensional coordinate table. The results show a very good agreement between the simulations and experimental results for both temperature and displacements values.